2013
DOI: 10.1111/sms.12152
|View full text |Cite
|
Sign up to set email alerts
|

Amlodipine reduces blood pressure during dynamic resistance exercise in hypertensive patients

Abstract: This study investigated the effect of the dihydropyridine calcium channel antagonist, amlodipine, on blood pressure (BP) during resistance exercise performed at different intensities in hypertensives. Eleven hypertensives underwent 4 weeks of placebo and amlodipine (random double-blinded crossover design). In each phase, they performed knee extension exercise until exhaustion following three protocols: one set at 100% of 1 RM (repetition maximum), three sets at 80% of 1 RM, and three sets at 40% of 1 RM. Intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…Many edible fruits and herbs contain UA, which is a bioactive phyto-constituent [ 20 , 32 , 33 , 34 , 35 ] and is also used in anti-obesity herbal medicines [ 21 ]. UA appear to strongly inhibit body fat gain in obese humans and animals [ 26 , 27 ]. Similar to these previous results, we observed significant changes in body fat percentage, but no changes in body weight ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many edible fruits and herbs contain UA, which is a bioactive phyto-constituent [ 20 , 32 , 33 , 34 , 35 ] and is also used in anti-obesity herbal medicines [ 21 ]. UA appear to strongly inhibit body fat gain in obese humans and animals [ 26 , 27 ]. Similar to these previous results, we observed significant changes in body fat percentage, but no changes in body weight ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants performed the RT program for 8 weeks using free weights and machines under the supervision of a trained instructor, who directed stretching exercises as a warm up to prevent soft tissue injuries and ensure subject safety. The accuracy of a prediction equation to estimate 1 repetition maximum intensity (1RM) until executed to fatigue was evaluated at each exercise session before starting the program [ 27 ]. This RT program consisted of a total of 26 exercise types, with 13 upper-body (chin-up, lateral pull-down, bent over/up-right row, bench press, fly, cable cross-over, shoulder press, lateral raise, biceps curl, concentration curl, barbell elbow extension, and kick back) and 13 lower-body training exercises (squat, leg extension, leg press, sissy squat, leg curl, dead lift, stiff leg dead lift, lunges, back extension, seated/standing calf raise, sit-up, and abdominal crunch) to strengthen the extremities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Souza et al 20 found similar results when they had applied a single session of knee extension protocol until fatigue in individuals of both genders (47±2 years). They compared two groups of hypertensive patients.…”
Section: Discussionmentioning
confidence: 64%
“…Hypertension causes multiple structural and functional cardiovascular changes that modify responses to exercise, producing not only a greater increase of BP during resistance exercise execution, but also a slower recovery during the intervals (Nery et al, 2010); which may distinctly change BP responses to different RTPs. In addition, the use of anti-hypertensive medications also affects BP response to RTPs (Gomides et al, 2010a;Souza et al, 2015;Ash et al, 2017). Thus, the hypothesis that a W:R-equated RTP with an intermediate number of sets and rest intervals may produce a lower BP increase during its execution than the RTP recommended in the hypertensives' guidelines, should be tested.…”
Section: Introductionmentioning
confidence: 99%